In vivo validation of a computationally predicted conserved Ath5 Target Gene Set - Del Bene, Filippo; Ettwiller, Laurence; Wittbrodt, Joachim (PLoS Genetics, 2007)
Author SummaryTo establish regulatory gene networks that drive key biological processes is of crucial importance to identify the genes that are directly controlled by transcriptional regulators. Ideally, this can be accomplished by identifying the direct transcription factor binding site in the cis-regulatory regions of the respective target genes. However, problems related to the fact that the motifs recognized and bound by transcription factors are short (6-20 bp) and consequently found very frequently and spread all over the genome, have limited this approach. The transcription factor Ath5 is involved in the specification and differentiation of retinal ganglion cells in the developing vertebrate eye. We show that Ath5 directly regulates its own expression by binding to a small region of its proximal promoter that contains two identical motifs. Using this motif description, together with conservation across large evolutionary distances, we then searched in the genome for other target genes of Ath5 and predicted 166 direct target genes. We then validated a subset of these predictions both in vitro and in vivo. Our analysis therefore provides an example of computation prediction of transcriptional target genes. At the same time, the genes identified represent the most comprehensive list of effectors mediating the role of Ath5 during eye development.